Analisa Pencahayaan Alami Ruang Kerja Pada Gedung Perkantoran Dengan Software DIALux Evo 11.1 (Studi Kasus : Gedung Balai Kota, Tebing Tinggi) - Devi Yanti, Meliana; Safyan, Adi; Aiyub, Hendra (Jurnal Etnik: Ekonomi-Teknik, 2023)
Lighting is an important aspect of buildings, especially in office buildings. A office building as a work area requires adequate comfort and fulfils lighting standards so that users can perform their activities smoothly and have good productivity. According to the observations of the Balai Kota Teb ing Tinggi building, there are no other high-rise buildings around the building and the window opens on either side of the building using windows with clear glass but without shading devices resulting in the illumination or distribution of natural lighting leading to the room looks very good. This study aims to analyze the level of natural lighting in the office workspace of Balai Kota Tebing Tinggi whether it has met the lighting standard SNI 6197-2020 or not because the building is a government service center that has already met the requirements of lighting according to the standards that have been in force. The study was conducted using a quantitative method with a simulation approach using the Dialux evo 11.1 software. The results of the study showed that there were some workspaces that did not meet the standard due to the influence of several factors such as the conditions of the sky and the time at the time of the simulation.